Lithuanian Bible by Martin Ludwig Rhesa (1816) as Evidence of Unity between Evangelical Lutheran and Moravian Churches - Strungytė-Liugienė, Inga (Knygotyra, 2018)
[full article and abstract in Lithuanian; abstract in English]The copy of Lithuanian Bible printed in Heinrich Degen’s publishing house in Königsberg in 1816 (sign.: BS 17.0/1) has been found in the Unity Archives – Moravian Archives Herrnhut (Herrnhuter Unitätsarchive). This copy was not recorded in the national bibliography of Lithuanian books and did not play a role in the circulation of scholarly knowledge. Christian Friedrich Cunow, the preacher of the Moravian Church and the leader of Brethren Society (Brüdersozietät) of Königsberg, left a donation note in this copy (in the fore title) with the comment that he donates the copy of Lithuanian Bible printed Königsberg to the library of the Unity of the Brethren (Brüder-Unität). This note encouraged [the author of this article] to gather more information about the above person and provided an impetus to find out more about his relationship with the Königsberg Bible Society officially established in 1810. It was found that Cunow was the member of the Society, along with clergymen of traditional Evangelical Lutheran Church – Ludwig Martin Rhesa (1776–1840), Ludwig Ernst Borowski (1740–1831), Samuel Gottlieb Wald (1762–1825) and Carl August Wilhelm Werner (1763–1846). As a member of the Society, he had the following responsibilities: to communicate with the British Bible Society, provide reports to them, take care of support for the publication of Lithuanian Bible and its distribution in Prussian Lithuania. Perhaps the most intriguing fact left unnoticed and not highlighted in the historiography was that not only the members of the traditional Evangelical Lutheran Church, but also the follower of the Moravian Movement contributed to the efforts in publishing and distributing the Lithuanian Bible. Cunow’s involvement in the Königsberg Bible Society is considered as a sign of solidarity between the two denominations in Prussian Lithuania in the first half of the 19th century.
Keywords: Martin Ludwig Rhesa, Königsberg Bible Society, the Lithuanian Bible, Christian Friedrich Cunow, the Moravian Church, diaspora activities in Prussian Lithuania